Peran Penyedia Barang Langsung Dan Jasa oleh Dinas Pangan dan Pertanian Dalam Meningkatkan Produksi Padi di Kabupaten Sidoarjo - Rahmadani, Rafdiah Iftisyah; Mursyidah, Lailul; Hariyoko, Yusuf (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
Etymologically, the role means someone who performs an action where the action is expected by other people. This means that every action that each individual has has an important meaning for some people. The agency has several programs to increase rice production, starting from carrying out activities to control OPT (Plant Destruction Organisms), providing pesticide assistance, coordinating with related parties for irrigation arrangements and optimizing the use of water pumps. However, in carrying out its role, the Food and Agriculture Service has several obstacles encountered in the field, including the Service has not been able to ensure the availability of fertilizers, limitations in human resources and budgets that have caused rice production in Sidoarjo Regency to decline. This study used descriptive qualitative methods. The data were obtained through observation, documentation, and interviews with the Head of Facilities and Infrastructure, the Head of Planning, and a combination of farmer groups. Data analysis techniques in this study are data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the government's role as a direct provision of goods and services cannot be carried out optimally by the Food and Agriculture Service, especially in providing fertilizer according to the request of the farmers because the subsidized fertilizer stock provided by the Service is still incomplete. In addition, the Department of Food and Agriculture has not been able to provide a complete machine tool for farmer groups in Sidoarjo Regency.